PERBEDAAN BOBOT DAN UKURAN TUBUH KAMBING BOERAWA GRADE 1 UMUR SATU TAHUN DARI BEBERAPA PEJANTAN KAMBING BOER DI KECAMATAN SUMBEREJO - Ade Irma Suryani; Sulastri ,; Idalina Harris (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2016)
This research was conducted to know yearling weight and yearling body measurements of Boerawa grade 1 (G1) from some bucks, to estimate heritability, and to estimate breeding value (BV) of yearling weight and yearling body measurements of Boer bucks. Fifty tails Boerawa G1 from 5 tails Boer bucks was used as research sample decided by purposive sampling. Survey method was done in this research located at Sumberejo subdistrict began August up to September, 2015. Variables observed were yearling weight and yearling body measurements. The body measurements consist of circumference of chest, body length, and shoulder height. Yearling weight and yearling body measurements were adjusted to yearling weight and yearling body measurements corrected. The data corrected was used to estimate heritability of Boerawa G1 and to estimate Breeding Value of each Boer bucks. Result of this research indicated that the average of yearling weight 33,78 ± 1,19 kg, yearling circumference of chest 68,28 ± 3,20 cm, yearling body length 63,73 ± 2,17cm, and yearling shoulder height 63,72 ± 2,96 cm. Heritability of yearling weight 0,19 ± 0,40, yearling circumference of chest 0; 0,15 ± 0,38, yearling body length 0,20 ± 0,41; yearling shoulder height 0,17 ± 0,39. Breeding value of Bursan buck for yearling weight 34,06 kg, yearling circumference of chest 69,10 cm, yearling body length 64,02 cm, and yearling shoulder height 64,42 cm. The breeding value of Bursan buck was highest. It could be concluded that Bursan buck was the best Boer buck. Key word: Boer Buck, Boerawa, Yearling Body Weight, Yearling Body Measurements, Breeding Value